Analisis Kritis Putusan Pengadilan Tata Usaha Negara dalam Perselisihan Izin Pinjam Pakai Kawasan Hutan untuk Pembangunan PLTA Tampur - Alya Caesar Nurohma (Program Studi Ilmu Hukum, Universitas Kuningan, 2024)
The aim of this research is to analyze the Banda Aceh PTUN decision Number 7/G/LH/2019/PTUN.BNA which was issued on August 28 2019. This decision granted the lawsuit filed by the Indonesian Forum for the Environment (Walhi) against the Governor of Aceh regarding licensing in publishing Borrow-to-Use Forest Area Permit for the Construction of the Tampur-I Hydroelectric Power Plant (443 MW) covering an area of ​​4,407 Ha in the name of PT Kamirzu in Gayo Lues Regency, Aceh Tamiang Regency, and East Aceh Regency, Aceh Province. The research method used in the article is a case study with a qualitative approach with research using secondary data from several Banda Aceh PTUN decision documents Number 7/G/LH/2019/PTUN.BNA, in the form of journal articles and related news. As a result of this research, the Banda Aceh PTUN Panel of Judges decided that the Dispute Object was invalid, and required the Defendant to withdraw the Dispute Object. The use of forest land for development does not comply with applicable licensing regulations, and the use of forest land for development also does not reflect permits that function in the public interest